2016
DOI: 10.1177/0363546515617472
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Return to Play After the Nonoperative Management of Hamstring Injuries in Athletes

Abstract: Numerous determinants have an effect on return to play after a hamstring injury in athletes. It is important for sports professionals to be aware of those determinants to guide athletes through the rehabilitation process and refine return-to-play strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 28 publications
(192 reference statements)
1
37
0
1
Order By: Relevance
“…However, it has been demonstrated that both MRI and US provide detailed information about the HMC with respect to localization and characterization of injury [12][13][14]. Furthermore, clinical, MRI and US determinants were established in the literature that have an effect on the time to return to play after HMC injury in athletes [16]. On the other hand, it is important to realize that for an individual HMC injury none of these MRI and US determinants show a direct correlation with the time to return to play [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been demonstrated that both MRI and US provide detailed information about the HMC with respect to localization and characterization of injury [12][13][14]. Furthermore, clinical, MRI and US determinants were established in the literature that have an effect on the time to return to play after HMC injury in athletes [16]. On the other hand, it is important to realize that for an individual HMC injury none of these MRI and US determinants show a direct correlation with the time to return to play [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Both MRI and US provide detailed information about the HMC with respect to localization and characterization of injury [13]. In a recent systematic review [16] several clinical, MRI and US determinants were determined that are associated with a longer recovery time in nonoperative management of acute HMC injury (summarized in Table 1). However, it is important to realize that for an individual HMC injury none of these MRI and US determinants show a direct correlation with the time to return to play [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hamstrings represent the most often injured muscle group in athletes. 90,91 No established clinical criteria as yet predict a safe return to play. 92 The MSK radiologist therefore plays a crucial role in determining the extent of the injury and advising athletes on their expected duration of inactivity.…”
Section: Imaging and Return To Playmentioning
confidence: 99%
“…13,53 Specifically, limitations in active knee extension with the hip flexed at 90 degrees compared with the contralateral extremity may be particularly useful as both a diagnostic and prognostic tool, with limited active knee extension suggesting both the presence of injury and prolonged return to play. 63,64 Provocative tests, which may be useful to diagnose mild strains or proximal hamstring tendinopathy, include the Puranen-Orava test, the bent knee stretch test, and the modified bent knee stretch test. 65 The Puranen-Orava test involves actively stretching the hamstring muscle in the standing position with the hip flexed to approximately 90 degrees and the knee fully extended with the foot supported on a chair or examination table.…”
Section: Physical Exammentioning
confidence: 99%